Lateral versus Anterior TAR: A Prospective Cohort Pilot Study of PROs and Re-Operation Rates. Issue 4 (16th October 2019) - Gagné, Oliver; Veljkovic, Andrea; Wing, Kevin; Penner, Murray J.; Alastair, S.E. Younger
Category: Ankle, Ankle Arthritis Introduction/Purpose: Recent advances in arthroplasty for the hip and the knee have motivated modern foot and ankle research to perfect the implant and technique for the optimal total ankle replacement. Unlike in the hip where different approaches can be done with the same implants, the approach of a total ankle is intimately associated to the prosthetic design. The anterior and lateral approaches have pros and cons regarding their respective soft tissue complications, osteotomy necessity, orientation of the bone cut and gutter visualization. While both have been studied independently, very few reports have compared both in the same setting. We set out to quantify the PROs and re-operations of both groups. Methods: A prospective study was conducted from a single center between 2014 and 2018 including a total of 64 total ankles performed by one of four fellowship-trained foot and ankle surgeon. A baseline dataset of their demographic as well as baseline scores (AOS, AAS & SF-36) was documented as well as at the 6 months and yearly mark post-operatively. Re-operations were also reported and coded in the local database. The approach was determined by the surgeon's practice preference and patients were referred to surgeons as part of a central intake. Patients were included when they had a primary TAR in the timeframe noted and had a complete dataset up to at least the one year outcome. This cohort comprised 27 anterior and 37 lateral with balanced demographic for age (95%CI 63-67 yo) and gender (47% F). The lateral group had higher COFAS type arthritis, longer intraoperative time and adjunct procedures. Results: Comparing the two groups, it was noted that the anterior group had superior SF-36 scores at the one-year post- operative mark on both the physical and mental components. The difference was statistically significant and greater than the MCID. Otherwise, the two groups had similar AOS and AAS post-operative scores that were not statistically different. A total of 8 patients had a reoperation, 7 were from the lateral cohort and 1 from the anterior approach group. The lateral group had 3 surgical debridement for deep infection/wound complication, 2 ankle gutter/HO debridement and 2 lateral hardware removal. The anterior group had one ankle gutter/ HO debridement. Two of the above patients had two re-operations and one had three. Conclusion: This prospective pilot study outlines the early results of lateral versus anterior total ankle replacements. The risk of deep infection requiring reoperation was higher in the lateral group and the SF-36 scores one year after surgery were inferior to the anterior group. The lateral cohort had however significantly more pre-operative peritalar disease which was not balanced and likely affected those results. Patient experience based on PROs (AAS, AOS) otherwise is comparable. Future studies with longer prospective data need to be considered to have the power to draw significant conclusions.